Depredación de Saguinus leucopus (Mammalia: Primates) sobre Phyllomedusa venusta (Anura: Hylidae) en el Departamento de Caldas, Colombia (2014)
ABSTRACT: The Silvery-brown Tamarin, Saguinus leucopus, is a primate species from the Callitrichidae family, endemic to Colombia, and that has very little ecological information. Here we report on a new dietary component for the species from Departamento de Caldas, Colombia, been the first record of S. leucopus predating an amphibian species (Phyllomedusa venusta). Despite some records exist about tamarin predation on amphibians, this is the first for this endemic species, and it is probably related with its foraging type. This record represents a noteworthy record and contributes to the knowledge of the natural history of this species.